Expert Teachers as Digital Citizens: The Attitudes of Expert Teachers in the Digital World (Training and Practice : Journal of Educational Sciences, 2016)
In this present paper the Digital Citizenship competency of Hungarian expert teachers will be examined. After presenting different approaches of Digital Citizenship, such as ISTE Standards and Ribble’s definition, this paper introduces the model of ELTE PPK ITOK, 2013 where the three elements of Digital Citizenship (Digital presence, Digital lifestyle and Digital productivity) and the usage of Bloom’s taxonomy will be presented. That is followed by the introduction of the methodology of Digital Citizenship research 2014 and a few results of Digital presence, consisting of Access, Usage of tools and Communication.